Território e territorialidades da comunidade indígena Guarani Mbyá Tenondé Porã - Costa, Lidiana Cruz da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research has as its aim discuss new acceptations of territory concept through the analysis of politic speeches produced by Indian Leaders of Tekoa Tenondé Porã Indian Land. The resistance, conflict and adaptation forms will be the main aspects for the concept analysis, since its fundamental importance in producing a specific territory kind. The reflections shown in the work support themselves in a theoretic outline from multiple knowledge areas, comprehending the territory importance as a material and social base for various Indian communities. It's conclusive which the discontinuous demarcated lands were not what is called Indian territory, seeing its fragmentation, the real Indian territory is concerned to the joint of various lands in a unique territory, enabling the social production and reproduction of these peoples

Esta pesquisa teve como objetivo discutir novas acepções do conceito de território por meio da análise dos discursos políticos produzidos por lideranças indígenas da Terra indígena Guarani Tekoa Tenondé Porã. As formas de resistências, lutas e adaptações serão os aspectos centrais para a análise do conceito, visto sua fundamental importância na produção de um determinado tipo de território. As reflexões apresentadas apoiam-se em um arcabouço teórico proveniente das diversas áreas do conhecimento, compreendendo a importância do território como uma base material e social para diversas comunidades indígenas. Concluiu-se que as terras descontínuas demarcadas não são os chamados territórios indígenas, visto sua fragmentação, o real território indígena está atrelado à junção de diversas terras em um único território, possibilitando a produção e reprodução social desses povos
Keywords: Territorialidade humana; Indios; Comunidade